Chemometrics-Enabled Raman Spectrometric Qualitative Determination and Assessment of Biochemical Alterations during Early Prostate Cancer Proliferation in Model Tissue - Githaiga, John I.; Angeyo, Hudson K.; Kaduki, Kenneth A.; Bulimo, Wallace D. (Journal of Spectroscopy, 2020)
The use of Raman spectroscopy combined with multivariate chemometrics for disease diagnosis has attracted great attention from researchers in recent years. This is because it is a noninvasive and nondestructive detection approach with enhanced sensitivity. However, a major challenge when analyzing spectra from biological samples has been the detection of subtle biochemical alterations buried in background and fluorescence noise. This work reports a qualitative chemometrics-assisted investigation of subtle biochemical alterations associated with prostate malignancy in model biological tissue (metastatic androgen insensitive (PC3) and immortalized normal (PNT1a) prostate cell lines). Raman spectra were acquired from PC3 and PNT1a cells at various stages of growth, and their biochemical alterations were determined from difference spectra between the two cell lines (for prominent alterations) and principal component analysis (PCA) (for subtle alterations). The Raman difference spectra were computed by subtracting the normalized mean spectral intensities of PNT1a cells from the normalized mean spectral intensities of PC3 cells. These difference spectra revealed prominent biochemical alterations associated with the malignant PC3 cells at 566 ± 0.70 cm−1, 630 cm−1, 1370 ± 0.86 cm−1, and 1618 ± 1.73 cm−1 bands. The band intensity ratios at 566 ± 0.70 cm−1 and 630 cm−1 suggested that prostate malignancy can be associated with an increase in relative amounts of nucleic acids and lipids, respectively, whereas those at 1370 ± 0.86 cm−1 and 1618 ± 1.73 cm−1 suggested that prostate malignancy can be associated with a decrease in relative amounts of saccharides and tryptophan, respectively. In the analysis using PCA, intermediate-order and high-order principal components (PCs) were used to extract the subtle biochemical fingerprints associated with the cell lines. This revealed subtle biochemical differences at 1076 cm−1, (1232, 1234 cm−1), (1276, 1278 cm−1), (1330, 1333 cm−1), (1434, 1442 cm−1), and (1471, 1479 cm−1). The band intensity ratios at 1076 cm−1 and 1232 cm−1 suggested that prostate malignancy can be associated with an increase in subtle amounts of nucleic acids and amide III components, respectively. The method reported here has demonstrated that subtle biochemical alterations can be extracted from Raman spectra of normal and malignant cell lines. The identified subtle bands could play an important role in quantitative monitoring of early biomarker alterations associated with prostate cancer proliferation.